A demographic study on gender related differences in adverse drug reactions of a tertiary care teaching hospital - Prasad, Raja Vikram; Pasha, M. A. Mushtaq; Fatima, Afsar; Deepalatha, C. (International Journal Of Community Medicine And Public Health, 2017)
Background: As a part of pharmacovigilance program of India (PvPI) adverse drug reactions (ADRs) are cause of mortality and morbidity in patients unnoticed, which is a part of WHO program for International Drug Safety Monitoring across world. ADRs are considered to be among top 10 causes for mortality. The reason for sex difference in medication response is multi factorial with wide range of aspects like steroid hormones, organ physiology to psychology and socio-cultural factors. The aim was to study on gender related differences in adverse drug reactions in patients attending tertiary care teaching hospital at Nandyal. Methods: ADR cases were collected from multicenter health care units from tertiary care teaching hospital. ADRs were reported in ADR notification forms or yellow form, CDSCO forms are used to report ADR to Regional pharmacovigilance center. Causality assessment of the ADRs was done based on WHO-UMC causality assessment scale using modified Hartwig and Seigel scale. Results: In the 30 ADR reports collected 21 reports (70%) are of female patients and 9 reports (30%) are of male patients. According to WHO-UMC scale 20 (70%) of Adverse drug reactions were falling into PROBABLE, while 10 (30%) ADR’s are CERTAIN. In 21 females, ADR reports were due to 15(76.43%) Antibiotics, 2 (9.52%) NSAID’s, 2 (9.52%) proton pump inhibitors, 2 (9.52%) anti-convulsants. In 9 males, ADR reports were due to 5 (55.5%) Antibiotics, 2 (22.22%) NSAID’s, 2 (22.22%) anti-convulsants. Conclusions: ADRs are the common occurrences but ADR monitoring helps in prevention of morbidity and mortality in patients. The most commonly affected gender is among female patients, as they are more exposed to drugs starting their journey right from the childhood, pregnancy till their adult menopausal stage.